20 Years of South African Democracy - MISTRA, Mistra (Mapungubwe Institute for Strategic Reflection (MISTRA), The, 2016)
This publication is the outcome of a conference marking the beginning of South Africa's third decade of democracy hosted in November 2014 by The Mapungubwe Institute for Strategic Reflection (MISTRA)RA) and the Thabo Mbeki African Leadership Institute (TMALI) at the University of South Africa (Unisa). The conference was entitled 20 Years of South African Democracy: So Where to Now? The main focus of the conference was projective reflections into the next two decades of democracy. It aimed to deal with the theoretical perspectives underpinning the state of South Africa in two decades of democracy and, most importantly, prospects for the future.